Speciation and hybridisation in skuas (Catharacta spp.) - Ritz, Markus (2009)
This study investigated the evolution of southern hemisphere skua taxa (Catharacta spp.) and revealed the modes and patterns of speciation in this group of seabirds. A hybrid zone between two species was investigated in more detail using AFLP to discriminate between species and their hybrids. This assignment could be used to uncover the degree of admixture and patterns of gene flow between both taxa. Skuas colonised the southern hemisphere before 220,000yBP, probably around the glaciation maximum at 250,000yBP. Diversification was rapid between 210,000 – 150,000yBP and coincided with a glacial period spanning 230,000 – 150,000yBP. The oldest taxon is most likely the South Polar Skua (Catharacta maccormicki), of which the Brown Skua (C. a. lonnbergi) split off first. The Tristan Skua (C. antacrtica hamiltoni) diverged from Atlantic populations of Brown Skuas and the Chilean Skua (C. chilensis) most likely originated from long-distance colonisation by Tristan Skuas to South America. The origin of the Falkland Skua (C. antarctica antarctica) is the least well defined of the southern taxa and the taxon may be the result of immigration from surrounding populations of several taxa. All taxa and many populations were significantly differentiated from each other. The South Polar Skua is the most homogenous taxon, while the Brown Skuas shows strong phylogeographic structure across its circum-Antarctic range. Evidence for gene flow was detected between most neighbouring population pairs of different taxa. This agrees with actual observations of limited hybridisation between Chilean Skua and Falkland Skua, South Polar Skua and Chilean Skua and extensive hybridisation between South Polar Skua and Brown Skua. The southern taxa do not deserve species status after the strict application of the Biological Species Concept but can be treated as species following the Comprehensive Biological Species Concept. Even so, the strong mitochondrial differentiation of the Brown Skua is not reflected by its current taxonomy.